TRENDS IN THE DEVELOPMENT OF THE RESTAURANT INDUSTRY IN KHARKIV (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
The article analyzes the current state of the restaurant services market in Ukraine and Kharkiv. The key problems and prospects for the development of the hospitality industry in the present are considered. It is emphasized that as a result of the full-scale russian invasion of Ukraine, the hospitality industry has become one of the most damaged sectors of the State's economy, and the conditions for the functioning of restaurant business establishments have become much more complicated. A significant differentiation in the impact of the war on the restaurant business in different regions of Ukraine was found. In addition, it is determined that the restaurant services market has undergone redistribution, and currently the largest number of restaurant establishments is located in the western regions of Ukraine. Having studied the restaurant sector of Kharkiv, it can be noted that, as of today, the city's restaurant services market shows a significant increase in the number of business entities of the following types: coffee shops, cafes, snack bars, and buffets. In addition, an increase in the number of restaurant establishments of various segments has been identified. However, it is noted that the share of medium-sized businesses is the largest, compared to the low and premium segments of establishments. The breadth of the range of restaurant services provided by the restaurant business establishments in Kharkiv was studied. Taking into account the data obtained during the study, the overall range of services was noted to be quite wide. At the same time, a large number of establishments offering a wide range of mandatory and additional services were not identified. Therefore, it was assumed that the consumer market in Kharkiv still needs to be transformed to improve the level of service provision. In conclusion, as a result of the overall data analysis, it was noted that the city's hospitality industry has prospects for dynamic development, and Kharkiv itself is an interesting tourist destination.
Keywords: hospitality industry; restaurant business establishments; business entities; development trends